A study of synthesis and properties of manganese-containing oxide coatings on alloy VT1-0 - Sakhnenko, Nikolay; Ved, Maryna; Karakurkchi, Ann; Galak, Alexander (Eastern-European Journal of Enterprise Technologies, 2016)
The study has substantiated the choice of components of manganese–containing electrolytes and their rational concentrations as well as determined the current density range for one–step plasma electrolytic oxidation of the VT1–0 alloy. Oxidation with mixed oxides produced coatings of different compositions and surface morphology. It has been shown that control over the chemical and phase compositions of coatings, the surface topography, and the grain size as well as incorporation of manganese oxides into a coating can be achieved by varying the concentration of the electrolyte and the oxidation parameters. Adding manganese sulfate to a pyrophosphate electrolyte has proved to be valuable for enhancing the content of the alloying component in the oxide layer and for reducing the concentrations of potassium and impurities. An increase in the current density of plasma electrolytic oxidation has been found to promote the formation of the oxide layer with a more developed surface area that is characterized by alternating torus–like inclusions and nanoporous sections. By studying the distribution of the content elements throughout the thickness of the oxide coating, it has been determined that manganese is uniformly distributed in the surface layer, but phosphorus is mainly located at the oxide–solution interface. It has been found that the synthesized mixed oxide coatings of manganese and titanium are highly resistant to abrasion. Incorporation of manganese has proved to reduce the grain size and improve the surface development, which facilitates catalytic activities in the oxidation reactions of carbon monoxide. The resulting materials can be used in process systems of catalytic purification.